Sleep Quality in the Survivors of COVID-19 - Farideh Bastani; Aida Amirijavid (Iran University of Medical Sciences, 2023)
Background: After being discharged from the hospital, some people recovering from COVID-19 may suffer complications and problems. This study was conducted to determine the sleep quality in the survivors of COVID-19 discharged from the hospital. Methods: This descriptive cross-sectional study was conducted in Imam Khomeini Sarab Hospital in East Azerbaijan Province, Iran, in 2022. The study sample was 222 survivors of COVID-19, discharged from the hospital for at least a month. The subjects were recruited by continuous sampling method. The data were collected by a demographic and disease-related questionnaire and the Pittsburgh sleep quality index (PSQI). The collected data were analyzed by the independent t-test, analysis of variance, and Scheffé post-hoc test in SPSS software, version 20. The significance level was set at P≤0.05.  Results: Among the subjects, 94(42.3%) were men, and 128(57.7%) were women. The age of the respondents was 50.32±16.75 years. About 84.2% of the study subjects obtained a total sleep quality score of more than 5, which means poor sleep quality. Also the mean sleep quality score of the research subjects was 9.19±3.68, indicating poor sleep quality. Significant relationships existed between sleep quality and most demographic and disease characteristics (P<0.001). Conclusion: Considering the poor quality of sleep of the survivors of COVID-19 after discharge from the hospital, it is suggested to give sufficient training to these patients before discharge to help them sleep comfortably, and if necessary, plan to refer them to a doctor.